The internet, expert patients and medical practice: an analysis of the literature - Helena Beatriz da Rocha Garbin; André de Faria Pereira Neto; Maria Cristina Rodrigues Guilam; David Eliff (Faculdade de Medicina de Botucatu (Unesp), 2008)
Over recent years, the world has witnessed a wide-ranging technological transformation that has substantially expanded the access to information, especially through the internet. In the field of healthcare, more and more information is available. Access to technical-scientific information, along with increased educational levels among the public, has given rise to patients who search for information about their diagnoses, diseases, symptoms, medications and costs of hospitalization and treatment: expert patients. This article discusses the way in which information obtained through the internet modifies or interferes with the doctor-patient relationship. Thus, the controversy between Freidson and Haug regarding the deprofessionalization of doctors is resurrected. Methodologically, we analyzed the opinions of authors who published articles on this topic between 1997 and 2005, in two important English academic journals in this field. We concluded that the positions found were distinct and even adversarial. In Brazil, despite digital exclusion, this question needs to be analyzed.